IMPLEMENTASI PEMBEBASAN BERSYARAT TERHADAP PROGRAM PEMBINAAN NARAPIDANA TINDAK PIDANA NARKOTIKA: Di Lembaga Pemasyarakatan Kelas II B Klaten - Adhitya Pradana; Eko Nurharyanto; Sigit Herman Binaji (Kajian Hukum, 2025)
The Corrections Law aims to: guarantees for the protection of the rights of prisoners and children; Improving the quality of personality and independence of inmates so that they realize their mistakes, improve themselves, and not repeat criminal acts, so that they can be accepted again by the community, can live normally as good, law-abiding, responsible citizens, and can play an active role in development; and Providing protection to the community from repetition of criminal acts. In accordance with Law Number 22 of 2022 concerning Corrections The purpose of this research is to find out and analyze the implementation of conditional release in the development of convicts for narcotics crimes (In Lembaga Pemasyarakatan Kelas II B Klaten) and to find out and analyze the obstacles and appropriate steps to overcome these obstacles. This research is descriptive juridical-normative legal research with a qualitative approach. The data collection method is through library research and field studies, namely making a list of questions and interviews, then analyzed using a qualitative descriptive analysis method. The research results show that coaching is carried out in 2 forms, namely personality coaching and independence coaching. The implementation of the conditional release process is in accordance with statutory regulations both administratively and substantively. In applying for Conditional Release, an online system has been used through the Correctional Database System Factors that become obstacles to the implementation of conditional release are related to administrative and substantive requirements in the process of applying for conditional release as well as related to development programs that are less than optimal so that there are still disciplinary violations in correctional institutions. The solution is to take a persuasive approach to prisoners to complete administrative requirements and improve training facilities and infrastructure, improve the quality of officers' abilities, support and assistance from related agencies.